Bovine Colostrum Silage: Physicochemical and Microbiological Characteristics at Different Fermentation Times - Kraus, Rosana Basso; dos Santos, Pedro Rassier; Krummenauer, Amanda; Palhares, Kevin Eduardo; Lima, Helenice Gonzalez de; Ladeira, Sílvia Regina Leal; Pereira, Giselda Maria; Dors, Giniani Carla; Nascente, Patrícia da Silva; Lund, Rafael Guerra (Frontiers in Microbiology, 2021)
Bovine colostrum silage (BCS) is a technique used by milk producers for the conservation of bovine colostrum. However, it is necessary to ensure the safety and quality of bovine colostrum silage, as this food will be supplied to the animals. This study aimed to compare the physicochemical and microbiological compositions of colostrum silage at different fermentation times with milk and bovine colostrum (BC) quality parameters. BC samples were obtained from Jersey animals from one dairy farm. The BC samples (n=21) were placed in 500-mL plastic bottles, stored vertically and anaerobically fermented for periods of 61 to 437 days. The following parameters of the physicochemical composition of the bovine colostrum silage were evaluated: acidity, protein, total solids and ash, using the methodologies of Adolfo Lutz Institute (2008). The microbiological analysis was developed according to the methodology proposed by Saalfeld et al. (2013), with adaptations. The acidity, total solids and protein over fermentation time (group 1: 61 to 154, group 2: 200 to 273 and group 3: 280 to 437 days) were not significantly different (P > 0.05). The ash content was significantly different (P < 0.05) in groups 1 and 3 and showed a decrease (moderate negative correlation of -0.63) with increasing fermentation time. Positive correlations were observed between total solids and the protein and ash contents. The genus of microorganisms with the highest occurrence was Lactobacillus spp. (95.2% of BCS) and those of lesser occurrence included Escherichia spp., Actinomadura spp., Streptococcus spp. and Leuconostoc spp. (4.8% of BCS). BCS has a physicochemical composition similar to BC and showed changes during the fermentation period; however, the presence of pathogenic microorganisms in bovine colostrum silages reinforces the need to further explore the quality parameters for BCS to ensure the safety of animals who receive this food.